2021
DOI: 10.1101/2021.10.29.466539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intracellular pH links energy metabolism to lymphocyte death and proliferation

Abstract: Many biological processes are controlled by cell death and proliferation. Previous evidence suggests that cell proliferation and death by apoptosis are regulated by separate pathways. The present study found that cellular pH was positively correlated with proliferation but negatively with apoptosis. Alkaline treatments enhanced lymphocyte proliferation in response to antigen challenge in vivo and in in vitro cultures, whereas acid treatments induced apoptosis. Low pH was incompatible with the survival of highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
(247 reference statements)
0
1
0
Order By: Relevance
“…Several studies have reported the existence of a link between the regulation of intracellular acidity and the reduction in cell death [ 58 , 59 , 60 , 61 ]. Therefore, in order to minimize toxic intracellular acidity, tumor cells must regulate the extrusion mechanisms of H ions, which increase pH .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the existence of a link between the regulation of intracellular acidity and the reduction in cell death [ 58 , 59 , 60 , 61 ]. Therefore, in order to minimize toxic intracellular acidity, tumor cells must regulate the extrusion mechanisms of H ions, which increase pH .…”
Section: Resultsmentioning
confidence: 99%